The effect of maturity on some physical and chemical properties of carabao mangoes (Mangifera indica Linn. Var. Carabao) - Carino, Lourmina A.; De Leon, Sonia Y. (1964)
(NO ABSTRACT)
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Mango -- Philippines